Tool design for low-frequency vibration cutting on surface property - Nakamura, Shogo; Nakanishi, Kenichi; Ohara, Kenji; Nakamura, Yoshikatsu; Ren, Zongwei; Kizaki, Toru; Sugita, Naohiko (Frontiers in Manufacturing Technology, 2023)
Low-frequency vibration cutting is a machining technology in which chips are broken by applying periodic vibrations along a specific axis. Periodic vibration deteriorates the surface roughness and roundness of the workpiece when compared to without vibration cutting. In this study, the properties of a machined surface under low-frequency vibration were simulated. Based on the simulation results, a tool was designed to reduce the effects of periodic vibration on the surface properties. Actual machining experiments were conducted using the proposed tool to clarify the relationship between tool shape, surface roughness, and roundness under low-frequency vibration. Using the proposed tool on low-frequency vibration cutting, the surface roughness was reduced (from 5.74 µm to .94 µm in Ra and 23.09 µm–6.66 µm in Rz), average roundness improved (from 4.73 µm to 2.95 µm), and maximum roundness decreased (from 15.34 µm to 3.61 µm) compared with those of the conventional tool.